Imaging of Bone Perfusion and Metabolism in Subjects Undergoing Total Ankle Arthroplasty Using 18F-Fluoride Positron Emission Tomography. (December 2019) - Dyke, Jonathan P.; Garfinkel, Jonathan H.; Volpert, Lauren; Sanders, Austin; Newcomer, Meghan; Dutruel, Silvina P.; Sofka, Carolyn M.; Ellis, Scott J.; Demetracopoulos, Constantine A.
Background: Total ankle arthroplasty (TAA) continues to exhibit a relatively high incidence of complications and need for revision surgery compared to knee and hip arthroplasty. One common mode of failure in TAA is talar component subsidence. This may be caused by disruption in the talar blood supply related to the operative technique. The purpose of this study was to quantify changes in talar bone perfusion and turnover before and after TAA with the INBONE II system using 18 F-fluoride positron emission tomography / computed tomography (PET/CT). Methods: Nine subjects (5 M/4 F) aged 68.9 ± 8.2 years were enrolled for 18 F-fluoride PET/CT imaging before and 3 months after TAA. Regions of interest (ROI) were placed on the postoperative CT images in the body of the talus beneath the talar component and overlaid on the fused static PET images. Standard uptake values (SUVs) along with dynamic K1 (bone blood flow) and ki (bone metabolism or osteoblastic turnover) were calculated. Results: The SUV underneath the talar component compared to that measured at baseline before surgery was 1.93 ± 0.29 preoperatively vs 2.47 ± 0.37 postoperatively ( P > .05). K1 was 0.84 ± 0.16 mL/min/mL preoperatively vs 1.51 ± 0.23 mL/min/mL postoperatively ( P = .026). ki was constant at 0.09 ± 0.03 mL/min/mL preoperatively vs 0.12 ± 0.03 mL/min/mL postoperatively ( P > .05). Conclusion: Our study was the first to link 18 F-fluoride PET/CT with pre-post evaluation of total ankle replacements. The study quantified perfusion within the talus beneath the TAA implant supporting the hypothesis that perfusion of the talus remained intact after surgery. Level of Evidence: Level II, prospective cohort study with development of diagnostic criteria.